(3LQjeI GdJQHM ai GdJTQjY GdeUQi hGdebGQf (B/ s - (3Gjef eMeO GHhYdes; (3YeQ GdaGQhbs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3JfGhdJ gPg GdQSGdI OQGSI ebGQfI dLQjeI GdJQHM HGYJHGQgG ef GdLQGFe GdeGSI HfRGgI GdhXjaI GdYGeI (B: (3MjK JMQU ZGdHjI GdJTQjYGJ GdLfGFjI Ydi MeGjI gPg GdfRGgI ef cd eG jThHgG JOYjeG ddKbI ai ehXai GdOhdI hGLgRJgG GdeNJdaI (B: (3hbO GMJhJ GdQSGdI Ydi OQGSI ebGQfI dLQjeI GdJQHM ai cd ef GdJTQjY GdeUQi hGdJTQjYjf GdaQfSi hGdchjJi (B: (3hbO bSefG GdQSGdI Gdi aUd JegjOi hKdGKI GHhGH (B: (3MjK JfGhdfG ai GdaUd GdJegjOi GdJWhQ GdJTQjYi dLQGFe GdeGd GdYGe ai bGfhf GdYbhHGJ GdeUQi (B: (3HjfeG JfGhdfG ai GdHGH GdGhd GdeUdMI GdeMejI ai GdJQHM (B: (3Ke JfGhdfG ai GdHGH GdKGfi GQcGf LQjeI GdJQHM (B: (3Ke JfGhdfG ai GdHGH GdKGdK hGdGNjQ GdYbhHI GdebQQI dLQjeI GdJQHM (B: (3hNdUfG ai fgGjI GdQSGdI Gdi HYV GdJhUjGJ GdJi GaVJ GdjgG Jdc GdOQGSIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2006s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B314-332s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3LQjeI GdJQHMs; (3YbhHI GdJQHM s; (3LQGFe GdeGd GdYGe s; (3GdeUdMI GdeMejI aj GdJQHM s; (3UaI GdehXa GdYGe s; (3CQcGf LQjeI GdJQHM s; (3GdJTQjY GdaQfSj s; (3GdJTQjY GdchjJj s; (3GdJTQjY GdeUQj s; (3GdbUO GdLfGFj aj LQjeI GdJONds; (3GdYbhHI GdCUdjI ddJQHM s; (3LQjeI GdeTGQcI HGdYed s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs